2009
DOI: 10.1073/pnas.0903524106
|View full text |Cite
|
Sign up to set email alerts
|

Leptin derived from adipocytes in injured peripheral nerves facilitates development of neuropathic pain via macrophage stimulation

Abstract: Nerve injury may result in neuropathic pain, characterized by allodynia and hyperalgesia. Accumulating evidence suggests the existence of a molecular substrate for neuropathic pain produced by neurons, glia, and immune cells. Here, we show that leptin, an adipokine exclusively produced by adipocytes, is critical for the development of tactile allodynia through macrophage activation in mice with partial sciatic nerve ligation (PSL). PSL increased leptin expression in adipocytes distributed at the epineurium of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 34 publications
8
94
1
2
Order By: Relevance
“…The proinflammatory cytokine-like functions of leptin in OA [10,[44][45][46][47] could explain its role in peripheral sensitization. Second, animal models suggest an involvement of leptin in the pathogenesis of pain at the spinal level and a possible role in the development of neuropathic pain [28][29][30]. Our clinical results support these experimental findings in patients with lower limb OA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The proinflammatory cytokine-like functions of leptin in OA [10,[44][45][46][47] could explain its role in peripheral sensitization. Second, animal models suggest an involvement of leptin in the pathogenesis of pain at the spinal level and a possible role in the development of neuropathic pain [28][29][30]. Our clinical results support these experimental findings in patients with lower limb OA.…”
Section: Discussionsupporting
confidence: 81%
“…Leptin levels in peritoneal fluid correlated positively with pain severity in endometriosis patients [27]. Furthermore, recent studies in rodents [28][29][30] suggested that spinal leptin might be involved in the pathogenesis of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Among animals with ligation of the sciatic nerve, only those producing leptin manifest tactile allodynia (leptin-deficient ob/ob mice do not manifest allodynia) (27). In pain associated with knee osteoarthritis, leptin secreted in the infrapatellar (Hoffa's) fat can contribute to nociception (7).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may help explain how ibuprofen could play a role in "rewarding" but not "addiction." Dopaminergic receptors are important components of the cellular mechanisms of both opioid rewarding (Manzanedo et al, 2005) and nociception (Wood, 2006). Several brain regions including the NAc play an important role in cue-elicited rewardseeking behaviors including mCPP through regulation of the dopaminergic system (Fenu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, intracerebroventricular leptin infusion enhanced the rewarding effect of D-amphetamine (Hao et al, 2006), whereas exogenous leptin attenuated acute food deprivation-induced relapse to heroin seeking (Shalev et al, 2001). Leptin also mediated nociceptive behavior induced by peripheral nerve injury and induced pronociceptive mediators in rats with tactile allodynia (Maeda et al, 2009). Therefore, it would be of considerable interest to examine a cellular mechanism between leptin and glial expression in the NAc and its relationship with opioid analgesia and opioid rewarding.…”
Section: Introductionmentioning
confidence: 99%